Karakteristik Dadiah Susu Kerbau dan Susu Sapi - Mardhiyah, Azzahrah Khairunnisa; Mayandri, Fadhila; Putri, Dwi Hilda; Fevria, Resti; Farma, Siska Alicia; Advinda, Linda (Prosiding Seminar Nasional Biologi, 2021)
Another way to use milk is to process it into dadih. Dadih is a typical food of West Sumatra which comes from buffalo milk and is processed through a natural fermentation process by microorganisms that produce lactic acid in bamboo tubes. The purpose of this study was to distinguish the characteristics of dadih made from buffalo milk and cow’s milk. This research is descriptive research. The results of the initial study were started after 10 g of buffalo milk curd was wet, dried using an oven with a dry weight of 8.5 g. Meanwhile, cow’s milk curd has a wet weight of 10 g, after drying it becomes 4.9 g. The results of organoleptic test on taste, cow’s milk dadih has a more sour taste than buffalo milk dadih. The color of these two types of dadih is no different, yellowish white. The texture of buffalo milk dadih is thicker than cow’s milk dadih.